Voltage- and Temperature-Dependent Allosteric Modulation of α7 Nicotinic Receptors by PNU120596 - Sitzia, Fabrio; Brown, Jon T.; Randall, Andrew; Dunlop, John (Frontiers in Pharmacology, 2011)
Alpha7 nicotinic receptors (a7nAChR) are widely distributed throughout the central nervous system (CNS) and are found at particularly high levels in the hippocampus and cortex. Several lines of evidence indicate that pharmacological enhancement of a7nAChRs function could be a potential therapeutic route to alleviate disease-related cognitive deficits. A recent pharmacological approach adopted to increase a7nAChR activity has been to identify selective positive allosteric modulators (PAMs). a7nAChR PAMs have been divided into two classes: type I PAMs increase agonist potency with only subtle effects on kinetics, whereas type II agents produce additional dramatic effects on desensitization and deactivation kinetics. Here we report novel observations concerning the pharmacology of the canonical type II PAM, PNU120596. Using patch clamp analysis of acetylcholine (ACh)-mediated currents through recombinant rat a7nAChR we show that positive allosteric modulation measured in two different ways is greatly attenuated when the temperature is raised to near physiological levels. Furthermore, PNU120596 largely removes the strong inward rectification usually exhibited by a7nAChR-mediated responses.